TEKNIK KULTUR PAKAN ALAMI Chlorella sp. dan Rotifera sp. SKALA MASSAL DAN MANAJEMEN PEMBERIAN PAKAN ALAMI PADA LARVA KERAPU CANTANG - Imam Prayogo; Miftahol Arifin (Faculty of Science and Technology University Ibrahimy, 2015)
The purpose of this study is to know the techniques for natural food culture (Chlorella sp, Rotifera sp) mass scale and the management of natural feeding larvae Cantang grouper (Epinephelus sp) in Situbondo BPBAP which was held from 04 February to 04 May 2015. Fertilizer use is: UREA = 400 gr, ZA = 300 gr and TSP / SP-36 = 200 gr. After fertilization, tubs filled inoculant of Chlorella sp. as much as 20% streamed using 1-inch hose and pump with a capacity of 450 V until evenly distributed (marked in green on the entire surface of a body culture). Harvesting Chlorella sp. performed after the maintenance period 7 -8 days. Rotifer mass culture is done in an open bath with a capacity of 5 tonnes with the installation of oxygen (aeration), inlet and outlet pipes are equipped with stop valves. Before use, bath cleaned first, then filled with sea water as much as 3 tons and filled Chlorella sp 1 ton gradually. Harvesting is done if it had been passed through a maintenance period 4-5 days using planktonet measuring 300 microns. Distribution of Chlorella sp. Reviewed grouper larvae Cantang since D2 - D30 with a density of 15,000-20,000 cells / cc or ½ ton to 1 ton. Provision of Chlorella sp. conducted in the morning is 07.00 pm. While Rotifers sp. given the grouper larvae Cantang since D2 - D30 gradually namely on D2 = 2-5 ind / ml. While on D3 - D30 = 5-10 ind / ml. Giving Rotifers sp.dilakukan at 08.00 am.